Occult nodal metastasis in major salivary gland malignancy: An update from the National Cancer Database. (May 2022) - Tranchito, Eve; Cabrera, Claudia; Terry, Morgan; Li, Shawn; Thuener, Jason E.; Fowler, Nicole; Lavertu, Pierre; Teknos, Theodoros N.; Rezaee, Rod P.; Tamaki, Akina
Highlights: NCDB review for rate of occult nodal disease and survival in patients with salivary gland cancer. Most subtypes studied had an occult metastasis rate over 20%. Patients with evident or occult nodal disease had worse overall survival. Risk factors of occult nodal disease include late stage, older age, black or other minority race. Abstract: Objectives: Malignant salivary gland tumors are rare neoplasms that are vastly heterogenous in their histological patterns and clinical behaviors. As a consequence, studies have lacked the robust sample sizes needed to define treatment strategies. In this study, we used the National Cancer Database to identify the incidence of occult nodal metastasis and effect on overall survival for the most common malignant salivary gland subtypes. A retrospective review of patients in the National Cancer Database with primary site malignancies of major salivary glands between 2004 and 2016 was performed. Subjects included in the study underwent surgical treatment with and without adjuvant radiation and had complete information on TNM pathological stage. Materials and methods: 8, 689 patients with primary malignant salivary gland cancer were analyzed. The sample was stratified by histologic subtype. Univariate analysis of lymph node metastasis of the whole cohort showed a higher risk of death (p < 0.001), when compared to those without. Also when comparing occult vs evident metastasis, the risk of death was higher for the latter (p < 0.001). Results and conclusion: Occult cervical lymph node metastasis ranged from 14.9% to 35.8% in malignant salivary gland cancers, depending on histological subtype. Occult nodal metastasis was a poor prognostic factor with significantly worse overall survival.